Communication, expectations, and trust: An experiment with three media - Anna Lou Abatayo; John Lynham; Katerina Sherstyuk (Games, 2020)
We studied how communication media affect trust game play. Three popular media were considered: traditional face-to-face, Facebook groups, and anonymous online chat. We considered post-communication changes in players' expectations and preferences, and further analyzed the contents of group communications to understand the channels though which communication appears to improve trust and trustworthiness. For senders, the social, emotional, and game-relevant contents of communication all matter, significantly influencing both their expectations of fair return and preferences towards receivers. Receivers increased trustworthiness is mostly explained by their adherence to the norm of sending back a fair share of the amount received. These results do not qualitatively differ among the three communication media; while face-to-face had the largest volume of messages, all three media proved equally effective in enhancing trust and trustworthiness.
Keywords: C72; C92; D83; 330; communication technology; content analysis; laboratory experiments; trust games